Diabetes increases the risk of deep-vein thrombosis and pulmonary embolism - Chung, Wei-Sheng; Lin, Cheng-Li; Kao, Chia-Hung (Thrombosis and Haemostasis, 2015)
We evaluated the effects of diabetes on the risks of developing deep vein thrombosis (DVT) and pulmonary embolism (PE) in a nationwide, population-based cohort study in Taiwan. The patients with newly diagnosed type 2 diabetes mellitus (T2DM) were identified, and DM-free controls were randomly selected from the general population and frequency-matched according to age, sex, and index year by using the records of the Longitudinal Health Insurance Database between 2000 and 2011. Both cohorts were followed up until the end of 2011 to measure the incidence of DVT and PE. We analysed the risks of DVT and PE using Cox proportional-hazards regression models. The overall incidence of VTE was higher in the T2DM patients than in the controls (12.0 vs 7.51 per 10,000 person-years). The T2DM patients exhibited a 1.44-fold adjusted hazard ratio (aHR) of VTE development compared with the controls (95 % confidence interval [CI] = 1.27–1.63). The risks of DVT (aHR = 1.43, 95 % CI = 1.23–1.65) and PE (aHR = 1.52, 95 % CI = 1.22–1.90) were greater in the T2DM than those in the controls. The T2DM patients had a substantially higher risk of DVT (aHR = 5.10, 95 % CI = 3.12–8.32) and PE (aHR = 7.50, 95 % CI = 3.29–17.1) development than the controls did in adults aged 49 years and younger. In conclusion, the longitudinal nationwide cohort study indicated that T2DM patients carried greater risks of developing VTE than did the general population.
Keywords: Diabetes mellitus (DM); deep vein thrombosis (DVT); pulmonary embolism (PE)